Methodology for defining homogeneous water bodies for management purposes. (December 2021) - Schourup-Kristensen, Vibe; Maar, Marie; Larsen, Janus; Mohn, Christian; Murawski, Jens; She, Jun; Jakobsen, Hans H.
Abstract: European legislation requires monitoring of toxic algae in marine areas where shellfish are harvested for consumption. Monitoring assumes the existence of homogeneous water bodies, the definition of which have important implications for stakeholders and consumers. Yet, the definition of homogeneous water bodies remains unclear. Here we present a methodology to divide coastal and estuarine waters into homogeneous water bodies to monitor toxic algae. The proposed method is mainly based on water transport, and secondarily on oceanographic characteristics; salinity and sea surface height. We apply the methodology to the Limfjord in Denmark and demonstrate its usefulness in areas with a complicated coastal morphology. The oceanographic descriptors applied in the method are standard outputs from coastal hydrodynamical models. Provided that validated and high resolution model output is available for a given area, the technique is thus adaptable to other morphologically and oceanographically complicated estuarine and coastal areas where toxic algae monitoring is necessary. Highlights: Homogeneous water bodies are defined by modeled oceanographic properties. A practical method for toxic algae coastal management in complex water bodies An unstructured coastal hydrodynamical model is applied to the Limfjord, Denmark.